Effect of glucose on assimilatory sulphate reduction in Arabidopsis thaliana roots - Hesse, Holger (Journal of experimental botany, 2003)
With the aim of analysing the relative importance of sugar supply and nitrogen nutrition for the regulation of sulphate assimilation, the regulation of adenosine 5'-phosphosulphate reductase (APR), a key enzyme of sulphate reduction in plants, was studied. Glucose feeding experiments with Arabidopsis thaliana cultivated with and without a nitrogen source were performed. After a 38 h dark period, APR mRNA, protein, and enzymatic activity levels decreased dramatically in roots. The addition of 0.5% (w/v) glucose to the culture medium resulted in an increase of APR levels in roots (mRNA, protein and activity), comparable to those of plants kept under normal light conditions. Treatment of roots with d-sorbitol or d-mannitol did not increase APR activity, indicating that osmotic stress was not involved in APR regulation. The addition of O-acetyl-l-serine (OAS) also quickly and transiently increased APR levels (mRNA, protein, and activity). Feeding plants with a combination of glucose and OAS resulted in a more than additive induction of APR activity. Contrary to nitrate reductase, APR was also increased by glucose in N-deficient plants, indicating that this effect was independent of nitrate assimilation. [35S]-sulphate feeding experiments showed that the addition of glucose to dark-treated roots resulted in an increased incorporation of [35S] into thiols and proteins, which corresponded to the increased levels of APR activity. Under N-deficient conditions, glucose also increased thiol labelling, but did not increase the incorporation of label into proteins. These results demonstrate that (i) exogenously supplied glucose can replace the function of photoassimilates in roots; (ii) APR is subject to co-ordinated metabolic control by carbon metabolism; (iii) positive sugar signalling overrides negative signalling from nitrate assimilation in APR regulation. Furthermore, signals originating from nitrogen and carbon metabolism regulate APR synergistically